Media Pencarian Tempat Persewaan Kendaraan Area Bandara Yogyakarta International Airport (YIA) - Aryanto, Salam; Pinandhita, Lazuardy Rahendra (Universitas Mercu Buana, 2024)
Yogyakarta International Airport (YIA) is one of the new airports located in Kulonprogo Regency. Access to the airport is still relatively difficult to reach by public transportation. An informative application is needed to assist prospective passengers in providing information. Therefore, an application based on artificial intelligence is made that is able to provide information and recommendations for vehicle rental places according to the vehicles that people want to use. This application will make it easier for visitors to take sightseeing trips to the area around the Yogyakarta International Airport (YIA) airport. This application utilizes the Simple Hill Climbing method, in utilizing the Simple Hill Climbing method the community will get information on the distance from the airport to the nearest to the furthest vehicle rental place. In the test results using the Black Box method goes according to the main design of the application and based on community assessments it shows that it is very effective to use with a success rate of 90% from the community's assessment as users.